Efecto de cuatro niveles de NPK aplicados en fertirriego sobre el rendimiento y calidad de Esparrago verde ( asparagus officinalis l.) cv uc 157 f1 en Virú, La Libertad - Murrugarra Valdiviezo, José Miguel (2012)
The main goal of this research was to determine the level of N, P and K applied by fertirrigation, to give the highest performance and quality of green asparagus cv. UC 157 F1• This experiment was installed in August 2010 in the company AGROINDUSTRIAS JOSYMAR S.A. C., located in Virú, La Libertad. The treatments to study were: first level at a dose of 105 kg de N.ha-1, 22 kg de P .ha -1 and 133 kg de K.ha-1, second level ata dose of 126 kg de N.ha"\ 26 kg de P.ha-1 and 159 kg de K.ha-1, third level ata dose of 147 kg de N.ha-1, 30 kg de P.ha-1 and 186 kg de K.ha-1; and the fourth level ata dose of 168 kg de N.ha-1, 35 kg de P.ha-1 and 212 kg de K.ha-1, applied to the soil by fertirrigation, in a design of complete blocks with five replications at random. The characteristics evaluated were the following: height of the plant, number of stems, number of bunches, number of unripe and ripe buds,total number of buds on first and second generation respectively, fresh weight of the foliage, weight of turions in the field and in the processing plant, commercial asparagus of denomination small, standard, large, extra large, jumbo and discarded asparagus.After analyzing the characteristics the conclusion was: 1) It was found highly significant response to the application of NPK in weight of turions in the field, commercial asparagus of denomination small, standard, large,extra large and discarded asparagus. 2) It was found response not significant to the application of NPK in commercial asparagus of denomination jumbo. 3) Under the dose of 105 kg de N.ha-1, 22 kg de P.ha-1 and 133 kg de K.ha-1 was the best production commercial asparagus of denomination standard (1904.60 kg.hé) and large (1169.00 kg.ha-1). 4) Under the dose of 126 kg de N.ha-1, 26 kg de P.ha-1 and 159 kg de K.ha-1 was the best weight of turions in the field (5421.20 kg.ha-1), the best production commercial asparagus of denomination small (495.60 kg.ha-1), extra large (732.80 kg.ha-1) jumbo (290.80 kg.ha-1) and the best production discarded asparagus (1345.20 kg.ha-1). 5) Under the dose of 126 kg de N.ha-1, 26 kg de P.ha-1 and 159 kg de K.ha-1; 147kg de N.ha-I, 30 kg de P.ha-1 and 186 kg de K.ha"1 and 168 kg de N.ha-1, 35 kg de P.ha-1 and 212 kg de K.ha-1 were the best productions commercial asparagus (4058.80 kg.ha-1, 4 043.80 kg.ha-1 and 4059.40 kg.ha-1 respectively).